The Growth and Bacteriocin Productions of Enterococcus Faecium Cultured in Aerobic and Anaerobic Conditions. Issue 1 (1st July 2022) - Ali, Muhamad; Artha, Melinda Sanggu; Suryadi, Muhamad Aidil Fadjar; Kisworo, Djoko; Amin, Muhamad
Abstract: Bacteriocins are antimicrobial compounds produced by diverse members of lactic acid bacteria (LAB). Bacteriocins can be used as food bio preservatives to increase the shelf life of food naturally by preventing or killing foodborne pathogens. One of the lactic acid bacteria that produce bacteriocin is Enterococcus faecium. Some LAB grown on semi-synthetic complex media such as MRS (de Mann Rogosa Sharpe) can make a high population of bacterial cells and relatively large bacteriocins. This study aimed to observe the growth of E. faecium on MRS and LB media under aerobic and anaerobic conditions. Cultures were performed for 4.5h, 5h, 5.5h, 6h, 6.5h, and 7h. The amount of bacteriocin produced was investigated by SDS-PAGE. Meanwhile, the inhibitory activity was measured against Listeria monocytogenes (LM). The results showed that E. faecium grew better in deMan Rogosa Sharp (MRS) medium under anaerobic conditions than in MRS medium under aerobic conditions as well as Luria Bertani (LB) media under aerobic and anaerobic conditions. The SDS-PAGE results showed a protein band measuring about 90 kDa, which was thought to be a bacteriocin. The inhibition test showed a clear zone in the LM culture, which indicated that the bacteria produced bacteriocins that could inhibit the growth of pathogenic bacteria.